CLIL in Action: Enhancing Academic Writing and Content Knowledge in Indonesian University Students - Ita Sarmita Samad; Ismail Ismail; Mutmainnah M. Dyah; Fatmawati Fatmawati (Universitas Muhammadiyah Enrekang, 2025)
This study investigates the effectiveness of Content and Language Integrated Learning (CLIL) in enhancing English writing proficiency and content knowledge among undergraduate students at Universitas Muhammadiyah Enrekang, Indonesia. A mixed-methods design was employed, combining quantitative pre-test and post-test assessments with qualitative surveys and classroom observations. The quantitative results revealed significant improvements in students' writing skills, particularly in structure, coherence, vocabulary, and grammar, with large effect sizes observed across these components. Additionally, students demonstrated considerable gains in their understanding of academic content, specifically in concept comprehension and terminology mastery. The qualitative data further supported these findings, with students reporting increased confidence in their academic writing and better integration of content knowledge and language. Classroom observations indicated that the structured writing tasks within CLIL lessons allowed students to better organize their thoughts and express complex ideas in English. However, the study also identified challenges, particularly in mastering academic terminology and integrating complex content with language learning. These findings suggest that CLIL is an effective pedagogical approach for improving both language proficiency and content knowledge, particularly in non-native English-speaking contexts. The study also highlights the importance of targeted vocabulary instruction and scaffolded content delivery to address the challenges faced by students. The results provide valuable insights into how CLIL can be adapted to enhance the quality of education in Indonesian higher education, particularly in regions with lower English proficiency. Future research could explore the long-term effects of CLIL and its potential for wider implementation across different academic disciplines in Indonesia.